Corporate governance in India: A systematic review and synthesis for future research - Faozi A. Almaqtari; Hamood Mohd. Al-Hattami; Khalid M. E. Al-Nuzaili; Mohammed A. Al-Bukhrani (Cogent Business & Management, 2020)
The present study aims to review systematically the state of the art of corporate governance in India. The study uses a sample of 161 published research papers extracted from 101 journals and 17 publishers' databases. The results indicated that 151 studies investigated the board of directors' issues, 90 studies analyzed ownership structure, 64 studies discussed audit committee attributes, and 11 articles studied audit quality. The results provided that among corporate governance issues, board and audit committee independence, foreign and institutional ownership have the highest and majority focus of research in India. In terms of the relationship of corporate governance with other areas, the results exhibited that financial performance has a major concern in prior research. The results also indicated that there is a lack of studies that have samples after 2015. Further, the results observed that there are numerous conceptual repetitive studies and the majority of the studies followed either descriptive statistics or basic regression analysis. The current study provides an insight for academicians, policymakers (e.g., Securities and Exchange Board of India and Ministry of Corporate Affairs-Government of India) research organizations and funding agencies of what has been done and what is left to be done. The study makes a novel contribution to the strand literature of corporate governance in India. It highlights the substantial knowledge gaps in this field and provides a potential agenda for academicians, research organizations, and funding agencies for future research.
Keywords: 650; Corporate governance; systematic review; India; board characteristics; audit committee attributes; ownership structure; audit quality